Inner speech in the daily lives of people with aphasia - Alexander, Julianne M.; Hedrick, Tessa; Stark, Brielle C. (Frontiers in Psychology, 2024)
Introduction This exploratory, preliminary, feasibility study evaluated the extent to which adults with chronic aphasia (N = 23) report experiencing inner speech in their daily lives by leveraging experience sampling and survey methodology. Methods The presence of inner speech was assessed at 30 time-points and themes of inner speech at three time-points, over the course of three weeks. The relationship of inner speech to aphasia severity, demographic information (age, sex, years post-stroke), and insight into language impairment was evaluated. Results There was low attrition (<8%) and high compliance (>94%) for the study procedures, and inner speech was experienced in most sampled instances (>78%). The most common themes of inner speech experience across the weeks were ‘when remembering’, ‘to plan’, and ‘to motivate oneself’. There was no significant relationship identified between inner speech and aphasia severity, insight into language impairment, or demographic information. In conclusion, adults with aphasia tend to report experiencing inner speech often, with some shared themes (e.g., remembering, planning), and use inner speech to explore themes that are uncommon in young adults in other studies (e.g., to talk to themselves about health). Discussion High compliance and low attrition suggest design feasibility, and results emphasize the importance of collecting data in age-similar, non-brain-damaged peers as well as in adults with other neurogenic communication disorders to fully understand the experience and use of inner speech in daily life. Clinical implications and future directions are discussed.